2005
DOI: 10.1182/blood-2004-06-2385
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of graft-versus-host-disease and survival after HLA-identical sibling bone marrow transplantation in ethnic populations

Abstract: The association of ethnicity with the incidence of graft-versus-host disease (GVHD) and other clinical outcomes after transplantation is controversial. We compared the results of HLA-identical sibling bone marrow transplantations for leukemia, performed between 1990 and 1999, among different ethnic populations, including 562 Japanese, 829 white Americans, 71 African Americans, 195 Scandinavians, and 95 Irish. Results for adults and children were analyzed separately. Multivariate analyses of adult patients show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
96
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 18 publications
7
96
5
1
Order By: Relevance
“…In general, the Japanese population has a homogeneous genetic background and incidence and severity of GVHD is considered to be lower than that in western populations even in HSCT from MSD. 12 Recently, Rizzo et al 13 reported there are, in respect of risk factors, two types of LM after HSCT. The squamous cell carcinoma of the skin and oral cavity are clearly related with GVHD, whereas the non-squamous cell carcinoma is not related with GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the Japanese population has a homogeneous genetic background and incidence and severity of GVHD is considered to be lower than that in western populations even in HSCT from MSD. 12 Recently, Rizzo et al 13 reported there are, in respect of risk factors, two types of LM after HSCT. The squamous cell carcinoma of the skin and oral cavity are clearly related with GVHD, whereas the non-squamous cell carcinoma is not related with GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, regionalization and specialization has been shown to reduce TRM as well as acute and chronic GVHD. 22,23 In order to address this crucial question, we included three sibling case-control pairs in our study, all diagnosed with MLD. Thus, we were able to compare progression of the untreated disease with that in a sibling with the same mutations who had undergone HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…All of the patients in our study were Japanese, and many of them (75%) had received BM as a stem-cell graft. It is known that Japanese patients have a lower risk of developing acute GVHD, 30 and that BMT is associated with a decrease in the development of acute GVHD. 31 Without haplotype C-A-A ( Thus, the ethnic population or the stem-cell source might also affect the association between CTLA-4 polymorphisms and the development of acute GVHD.…”
Section: Discussionmentioning
confidence: 99%